Beneficial effects of autologous bone marrow-derived mesenchymal stem cells in naturally occurring tendinopathy. - Roger Kenneth Whealands Smith; Natalie Jayne Werling; Stephanie Georgina Dakin; Rafiqul Alam; Allen E Goodship; Jayesh Dudhia (PLoS ONE, 2013)
Tendon injuries are a common age-related degenerative condition where current treatment strategies fail to restore functionality and normal quality of life. This disease also occurs naturally in horses, with many similarities to human tendinopathy making it an ideal large animal model for human disease. Regenerative approaches are increasingly used to improve outcome involving mesenchymal stem cells (MSCs), supported by clinical data where injection of autologous bone marrow derived MSCs (BM-MSCs) suspended in marrow supernatant into injured tendons has halved the re-injury rate in racehorses. We hypothesized that stem cell therapy induces a matrix more closely resembling normal tendon than the fibrous scar tissue formed by natural repair. Twelve horses with career-ending naturally-occurring superficial digital flexor tendon injury were allocated randomly to treatment and control groups. 1X10(7) autologous BM-MSCs suspended in 2 ml of marrow supernatant were implanted into the damaged tendon of the treated group. The control group received the same volume of saline. Following a 6 month exercise programme horses were euthanized and tendons assessed for structural stiffness by non-destructive mechanical testing and for morphological and molecular composition. BM-MSC treated tendons exhibited statistically significant improvements in key parameters compared to saline-injected control tendons towards that of normal tendons and those in the contralateral limbs. Specifically, treated tendons had lower structural stiffness (p<0.05) although no significant difference in calculated modulus of elasticity, lower (improved) histological scoring of organisation (p<0.003) and crimp pattern (p<0.05), lower cellularity (p<0.007), DNA content (p<0.05), vascularity (p<0.03), water content (p<0.05), GAG content (p<0.05), and MMP-13 activity (p<0.02). Treatment with autologous MSCs in marrow supernatant therefore provides significant benefits compared to untreated tendon repair in enhancing normalisation of biomechanical, morphological, and compositional parameters. These data in natural disease, with no adverse findings, support the use of this treatment for human tendon injuries.